The Influence of Parent-Child Separation on the Development of Children: Evidence from the Survey of Migrant Children in Beijing - Bo, L. (Best Evidence in Chinese Education, 2020)
Based on a survey of 2,367 fourth-grade migrant children in Beijing’s functional development zone (2016-2017), this article explores the im-pact of parent-child separation on children’s development from three dimensions: academic performance, non-cognitive development, and physical health.